2023
DOI: 10.1891/rtnp-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

A Hermeneutic Phenomenological Study of Aesthetics in Nursing Practice Among Hospitalized Cancer Patients in Nepal

Abstract: Background:Aesthetics is the art of nursing that is expressive, subjective, and visible in the act of caring in nursing practice. Aesthetics in nursing practice satisfies holistic needs and achieves the quality of whole-person care.Purpose:The aim of this study is to describe the meanings of the lived experiences of cancer patients in terms of receiving care from the perspective of aesthetics in nursing practice.Methods:The hermeneutic phenomenological approach grounded on Gadamerian philosophy guided this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…These findings showed similarities with other studies17,33,35,37 exploring perspectives of aesthetics in nursing practice, such as showcasing trust, honorable behavior, true love, and respecting the patient's dignity, as the basis of effective communication between nurses and persons being nursed. However, due to the differences in age, developmental stages, and experiences between children in this study as compared with adult participants,17,33 children's understanding of some nursing aesthetics is found to be different from that of adults, and they are more inclined to sensibility and purity. Because underage children's attachment to home and family is beyond question, the hospital environment would seem very unfamiliar so that they could feel very insecure during hospitalization.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…These findings showed similarities with other studies17,33,35,37 exploring perspectives of aesthetics in nursing practice, such as showcasing trust, honorable behavior, true love, and respecting the patient's dignity, as the basis of effective communication between nurses and persons being nursed. However, due to the differences in age, developmental stages, and experiences between children in this study as compared with adult participants,17,33 children's understanding of some nursing aesthetics is found to be different from that of adults, and they are more inclined to sensibility and purity. Because underage children's attachment to home and family is beyond question, the hospital environment would seem very unfamiliar so that they could feel very insecure during hospitalization.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, as this study described the aesthetics of nursing from the perspective of children, it is worth noting that they are pupils who are in a learning state, and some treatments and nursing methods need their cooperation to be completed. Nurses can instruct correctly and sensibly without coercion or urging, which is not mentioned in other studies 17,33,35,37. A study has reported that urging or forcing children to cooperate with treatment can make children rebellious and insecure in the hospital 38…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations